2021
DOI: 10.1111/jph.13058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of biosynthesized silver nanoparticles from Larrea tridentata against Clavibacter michiganensis

Abstract: Green synthesis of silver nanoparticles (AgNPs) from plant extracts is simple, fast and environmentally friendly. In this study, an aqueous extract of fresh leaves from Larrea tridentata was evaluated as a possible source of reducing and stabilizing agents to obtain AgNPs. The synthesized nanoparticles were characterized by X-ray diffraction, revealing the metallic nature of Ag nanoparticles. Transmission electron microscopy (TEM) studies showed spherical nanoparticles with sizes below 28 nm. Furthermore, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Silver nanoparticles (AgNP) were obtained according to the methodology proposed by [ 18 ]. The nanoparticle characterization was carried out through powder X-ray diffraction, in a Rigaku Ultima IV diffractometer using radiation CuKα (λ = 1.5418 Å) at 40 kV and 44 mA, at a scanning speed of 0.02 (2θ/s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles (AgNP) were obtained according to the methodology proposed by [ 18 ]. The nanoparticle characterization was carried out through powder X-ray diffraction, in a Rigaku Ultima IV diffractometer using radiation CuKα (λ = 1.5418 Å) at 40 kV and 44 mA, at a scanning speed of 0.02 (2θ/s).…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous extracts from L. trindentata have proven to be excellent reducers of AgNO 3 . They contain compounds such as phenolic lignans, saponins, flavonoids, amino acids, and minerals, which can substitute toxic compounds in addition to acting as stabilizing agents, allowing the synthesis of functional nanoparticles [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For their part, Méndez-Andrade et al (2021) used an aqueous extract from L. tridentata leaves as a source for reducing and stabilizing agents to obtain silver nanoparticles, which exert bactericidal activity against Clavibacter michiganensis . The authors reported that, at a concentration of 50 mg/L, disease incidence did not exceed 20%, and disease severity was reduced by 36% [ 78 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Aqueous extracts of Larrea tridentata was used to synthesize silver nanoparticles against C. michiganensis subsp. michiganensis that proved effective with lowest disease incidence (Méndez-Andrade et al, 2022). Plant extracts of Thymus syriacus was used to form ZnO nanoparticles and their antibacterial activity was checked against plant pathogenic bacteria (Sahin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%